Fabrication and characterisation of alumina/aluminium composite materials with a nacre-like micro-layered architecture. (November 2022) - Wan, Hongbo; Leung, Nathanael; Jargalsaikhan, Urangua; Ho, Eric; Wang, Chaolin; Liu, Qiang; Peng, Hua-Xin; Su, Bo; Sui, Tan
Graphical abstract: Highlights: The manufacturing of alumina/aluminium composites with nacre-like micro-layered architectures, with ceramic fraction from 18% to 85%, was achieved. The composites exhibited superior strength (600 MPa) and fracture toughness (35 MPa.m 1/2 ). The nacre-like bioinspired composites exhibited significant extrinsic toughening mechanisms. This work investigated the effect of interface and microstructure on the mechanical performance. Abstract: Many natural materials demonstrate ideal design inspirations for the development of lightweight composite materials with excellent damage tolerance. One notable example is the layered architecture of nacre, which possesses toughness an order of magnitude higher than its constituent parts. Man-made nacre-like ceramic/polymer composites obtained through direct infiltration of polymer in ceramic scaffolds have been shown to produce improved mechanical properties over other composite architectures. Replacing the polymer phase with metal could provide higher damage tolerance but the infiltration of metal into complex ceramic scaffolds is difficult due to the surface tension of molten metal. To address this, bioinspired nacre-like micro-layered (µL) alumina scaffolds with different ceramic fractions from 18 to 85% were infiltrated with aluminium alloy 5083 via pressureless and squeeze casting infiltrations techniques. The scaffolds were created using a bi-directional freeze-casting and one-step densification method. As a result, the µL alumina/aluminium composites displayed significant extrinsic toughening mechanisms with both high strength and toughness. The mechanical performance was highly dependent on the interface, microstructure, and composition. The nacre-like composites with 18% alumina and AlN interface displayed a maximum resistance‐curve toughness up to around 70 MPa.m ½ (35 MPa.m ½ at the ASTM limit) and a flexural strength around 600 MPa.